Web-Based Educational Games for Teaching Basic Football Techniques in Secondary School Physical Education - Mukti, Jozuna Aziz Kusuma; Akhyar, Muhammad; Santosa, Eka Budhi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
The development of a web-based educational game for the teaching of Physical Education, Sports, and Health (Penjasorkes) represents an innovative approach aimed at enhancing student engagement and comprehension of fundamental soccer techniques, including passing, dribbling, and shooting. However, traditional methods in Physical Education classes often rely heavily on verbal instructions and textbooks, leading to low student motivation and limited mastery of basic techniques. This research employs a Research and Development (R&D) methodology based on the Alessi & Trollip model, which encompasses stages of planning, design, and development. The research subjects include media experts, content specialists, Penjasorkes teachers from high schools and vocational schools, and students as end users. The research involved two media experts, two content experts, three Penjasorkes teachers, and 93 students from high schools and vocational schools in the Boyolali region of Central Java. Data collection was conducted through observations and questionnaires, followed by qualitative and quantitative analysis. The alpha test results indicated a